School Broadcasting in Canada - Lambert, Richard, S. (Book collections on Project MUSE., 1963)
This book describes the origin, growth, and achievements of school broadcasting in Canada. The book is the first authoritative description, by the man largely responsible for its success, of an important and fruitful experiment in federal-provincial co-operation in the thorny field of education.